Sharing And Jumping Task In Collaborative Teaching And Learning Process - admin admin; Slamet Asari (Universitas Muhammadiyah Gresik, 2017)
Providing material in the forms of task in collaborative teaching and learning process is one way in tapping the potential of the student's ability both on the cognitive, affective or psychomotoric trait.The task material provided in this collaborative learning is to foster a dialogical situation, communicative atmosphere, mutual listening and learning among students. The material itself is an obligatory task which is in accordance with the capacity of each student. Material assignments or tasks in the learning process is not only as an evaluation tool but also as a tool triggering the implementation of the teaching procedures to deliver real results that makes the students understand and learn the actual learning. Therefore, the level of task must be considered to obtain real change for each student learning.